Hubungan Metalinguistik dengan Kemampuan Reading Comprehension Anak Kelas 2-6 SD di Surakarta - Sugiantoro, Dewi Citra; Triantoro Aji Pratomo, Hafidz (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Abstract Background: Reading comprehension exhibits a complex system that describes how different linguistic elements take part in reception and comprehension. Metalinguistics indirectly affects how one comprehends a passage. Objectives: The purpose of this study was to determine the relationship between metalinguistics and reading comprehension ability of children in grades 2-6 in Surakarta. Methods: This study is a type of quantitative research and uses a causality research design. In sampling using multistage sampling technique with a sample of 100 respondents. Data collection using questions then data processing using the spearman rank test. Results: This study uses the spearman rank analysis test because it is to determine the relationship between the two variables. With the results of the p value = 0.000, where the p value <0.05 then Ha (Alternative Hypothesis) is accepted, thus indicating that there is a significant relationship between metalinguistics and Reading Comprehension ability of children in grades 2-6 SD in Surakarta. The correlation coefficient of 0.51 is said to be strong because it falls into the interval. Conclusion: Based on the results of data analysis, it can be concluded that there is a strong relationship between metalinguistics and reading comprehension ability in grade 2-6 elementary school children. Keywords : Language, Metalinguistics, Reading Comprehension, Literacy